Histopathological study of placentae in intrauterine growth retardation pregnancies in a tertiary care hospital and correlation with fetal birth weight (Journal of Pathology of Nepal, 2017)
Background: Intra uterine Growth Retardation is the most significant factor of perinatal mortality. The aim of this study was to assess the histopathological changes in the placenta in association with IUGR and correlation with fetal birth weight.Materials and Methods: A total of 100 placentae were included. Twenty five normal placentae and 75 placentae were from IUGR pregnancies were included.Results: Intervillous fibrin deposition (64%), increased  syncytial knotting (64%), stromal fibrosis (65%), cytotrophoblastic hyperplasia (44%) and  basement membrane thickening (40%) were seen along with hypovascular villi and infraction were present in 32% and 28% respectively. These changes were seen less in the control group (p